MECHANISMS OF BACTERIAL CONFLICT: MOLECULAR INSIGHTS INTO BACTERIAL COMPETITION AND ANTIPHAGE DEFENCE - Bullen, Nathan (My University, 2024)
Many bacteria inhabit polymicrobial communities where competition for resources is fierce. To survive, they employ sophisticated systems to outcompete rivals and defend against threats. Here, I present three studies exploring the molecular mechanisms underlying unique aspects of microbial conflict, including interbacterial competition and defence against phage predation. This work highlights the complex and often nefarious strategies bacteria and their viruses (bacteriophages) use to succeed in their habitats. First, I characterize the effector repertoire of the H2 type VI secretion system of Pseudomonas aeruginosa, showing that this protein export pathway delivers at least six toxins directly into competing bacterial cells. I further show that one of these toxins, termed RhsP2, functions as an ADP-ribosyltransferase that elicits cell death through the modification of diverse non-coding RNAs, including tRNA and RNase P. These findings reveal a new mechanism of interbacterial antagonism and describe the first physiological role for the ADP-ribosylation of RNA. Second, with the help of collaborators, I explore how the pathogenic bacterium Enterococcus faecalis defends against bacteriophage predation. Using forward genetics, we identify one antiphage defence mechanism involving a type IV restriction enzyme (TIV-RE) encoded within a plasmid of the model strain V583. By isolating bacteriophage that can circumvent this defence, we also discover a novel family of anti-TIV-RE inhibitor proteins encoded by enterococcal phages. Finally, I explore the physiology of MuF toxins, a widespread family of polymorphic protein toxins encoded within prophages. I demonstrate that MuF toxins are antibacterial, inhibiting processes such as protein synthesis and cell division. Furthermore, I show that these toxins are trafficked into the phage capsid via their N-terminal MuF domains, poising them for delivery into host cells at the onset of infection. Although their precise role remains to be determined, this study lays the groundwork needed to fully characterize this intriguing family of antibacterial toxins.
Keywords: Microbial Conflict; Bacterial Competition; Antibacterial Toxins; Antiphage Defence; ADP-ribosyltransferases; Restriction Enzymes